Incidence of Hydatidosis in Slaughtered Animals and their Relation to Public Health at Baghdad Province - Abdulkareem Thamer Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Hydatid cysts disease is an important public health problem and economic losses especially at developingcountries such, Iraq. A study of incidence of hydatidosis in sheep and cattle, which are slaughtered foodanimals, was carried out at different areas of Baghdad province outside the government abattoirs, duringa period of 18 months from November 2016 to May 2018. Both slaughtered livestock animals (sheep andcattle) which are local breed of both sexes, they are of difference areas in boundary at Baghdad city, and withages having non descriptive features. Hand palpation and visual inspection were followed in this study. Atotal , 2594 carcasses were examined comprising 1632 sheep and 962 cattle, from these 33, 11 ( sheep andcattle) respectively were found to harbour the cysts, recording percentages of (2.0%, 1.1%) respectively. Thepredominant location cysts at the liver (48.4%, 45.4% ) in sheep and cattle respectively, next by the lungs ,in sheep and cattle (39.3%, 36.3%) respectively. Next to the mixed organs (liver + lung), the incidence was(18.1%) in cattle and (9.0%) in sheep. The percentage of cysts in heart of sheep was (3.0%) but in cattle itwas (0%) Zero. The results revealed that fertile cysts only, were present in sheep with (87.8%) fertility. Cystsin the organs ranged(1-13,2-7) in sheep and cattle respectively. It can be observed that , sheep play a majorrole for distributions the disease. Suggestive control measures and public health hazard were mentioned.